"Bodyminds reimagined: (Dis)ability, race, and gender in Black women's speculative fiction," by Sami Schalk - Lothian, Alexis (Transformative Works and Cultures, 2019)
Review of Sami Schalk. Bodyminds reimagined: (Dis)ability, race, and gender in Black women’s speculative fiction. Durham, NC: Duke University Press, 2018. Paperback, $23.95 (192p) ISBN 9780822370888.